Setting the top 10 priorities for obesity and weight-related research (POWeR): a stakeholder priority setting process - Butler, A; Astbury, N; Goddard, L; Hajizadeh, A; Seeber, P; Crawley, B; Aveyard, P; Jebb, S (BMJ Publishing Group, 2022)
Objectives To identify and prioritise the most impactful, unanswered questions for obesity and weight-related research.